Therapeutic Potential of Drug Delivery by Means of Lipid Nanoparticles: Reality or Illusion? - Uner, Melike; Damgali, Sukran; Ozdemir, Samet; Celik, BURAK; ÇELİK, BURAK (My University, 2017)
Background: Solid lipid nanoparticles (SLN) are colloidal drug carrier systems that contribute several properties required from a sophisticated drug delivery system for increasing drug bioavailability and providing effective therapy. Many advantages of SLN have been reported over traditional dosage forms and their colloidal counterparts since the early 1990s. They were optimized for oral drug delivery for the first time. The first SLN formulations were produced by reducing particle size of solid lipid microparticles by spray congealing technique in the late 1980s. Then, studies have been continued investigating for their different administration routes else including parenteral, transdermal, ocular, nasal, respiratory etc.